Analisis Proses Change Management Dengan Menggunakan Corporate Cholesterol Test Di Sutanraja Resort And Convention Center - kumaat, Arief (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
This research aims to analyze the Change Management process and identify health or cholesterol level through Corporate Cholesterol Test. Â From 9 department existed in Sutanraja Resort and Convention Center which already reviewed the health or cholesterol level through Corporate Cholesterol Test, it is known that there are 1 department that already have an indication of emerging diseases, that is Food and Beverage department, while the other 8 department can be said is still in healthy enough condition, with the details are: Sales and Marketing department is at a healthy condition; Accounting department, Human Resource department, Information Technology department, and Entertainment department are at a healthy enough condition; Front Office department, House Keeping department, and Engineering department are a healthy enough condition but began to lead to the emergence of the disease indications. Keywords: Change Management, Corporate Cholesterol Test, Sutanraja